Translational-rotational interaction in dynamics and thermodynamics of 2D atomic crystal with molecular impurity: Physics in Quantum Crystals - Antsygina, T.N.; Poltavskaya, M.I.; Chishko, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The interaction between the rotational degrees of freedom of a diatomic molecular impurity and the phonon excitations of a two-dimensional atomic matrix commensurate with a substrate is investigated theoretically. It is shown, that the translational-rotational interaction changes the form of the rotational kinetic energy operator as compared to the corresponding expression for a free rotator, and also renormalizes the parameters of the crystal field without change in its initial form. The contribution of the impurity rotational degrees of freedom to the low-temperature heat capacity for a dilute solution of diatomic molecules in an atomic two-dimensional matrix is calculated. The possibility of experimental observation of the effects obtained is discussed.